THE ROLE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS BETWEEN VARIABLES AT PT. MUJUR LESTARI - Robert Rico Marpaung; Nazaruddin Nazaruddin; Isfenti Sadalia (SEAN Institute, 2022)
As a company engaged in the oil palm plantation sector located in South Labuhanbatu Regency, North Sumatra, PT Mujur Lestari seeks to maintain productive employees, where employees are an important asset for the company because this type of company is labor intensive whose productivity also depends on the availability of labor. . However, unfortunately the company's efforts are still not good in retaining employees, where the data shows the level of employee turnover from 2015 to 2019 fluctuated. This is what prompted the authors to conduct research on the role of the Work Environment and Organizational Culture in increasing Organizational Commitment through Job Satisfaction as an intermediate variable. The research methodology used is path analysis using 2 independent variables (work environment and organizational culture), 1 moderation variable (job satisfaction) and 1 dependent variable (organizational commitment) using Smart PLS ver 2.3.8. The population in this study were all employees registered at PT Mujur Lestari, totaling 412 people. While the sampling method using the Hair Method as many as 40 people. The results of the research using the outer model show that no trimming is found, where all construct variables have proper validity and reliability. While the inner model found that the work environment directly affects job satisfaction, organizational culture influences job satisfaction, job satisfaction affects organizational commitment, Work Environment has no effect on Organizational Commitment and Organizational Culture has an effect on Organizational Commitment. While indirectly found that the Work Environment and Organizational Culture affect Organizational Commitment through Job Satisfaction as an intermediate variable.